2009
DOI: 10.1038/sj.bjc.6605398
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for delayed presentation and referral of symptomatic cancer: evidence for common cancers

Abstract: Background:It has been suggested that the known poorer survival from cancer in the United Kingdom, compared with other European countries, can be attributed to more advanced cancer stage at presentation. There is, therefore, a need to understand the diagnostic process, and to ascertain the risk factors for increased time to presentation.Methods:We report the results from two worldwide systematic reviews of the literature on patient-mediated and practitioner-mediated delays, identifying the factors that may inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
447
3
12

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 438 publications
(500 citation statements)
references
References 44 publications
38
447
3
12
Order By: Relevance
“…Most said the lump was not present all the time and could be felt on and off, raising doubts as to whether there was a lump in the first place and strengthening the belief that the lump was benign. Non-recognition of symptom seriousness is a common theme in patient delay (Burgess et al, 2001;McLeod et al, 2009;Lam et al, 2009). Absence of pain is usually assumed to indicate benign disease and therefore does not warrant a visit to the doctor (Burgess et al, 2001;McLeod et al, 2009;Lam et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most said the lump was not present all the time and could be felt on and off, raising doubts as to whether there was a lump in the first place and strengthening the belief that the lump was benign. Non-recognition of symptom seriousness is a common theme in patient delay (Burgess et al, 2001;McLeod et al, 2009;Lam et al, 2009). Absence of pain is usually assumed to indicate benign disease and therefore does not warrant a visit to the doctor (Burgess et al, 2001;McLeod et al, 2009;Lam et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Non-recognition of symptom seriousness is a common theme in patient delay (Burgess et al, 2001;McLeod et al, 2009;Lam et al, 2009). Absence of pain is usually assumed to indicate benign disease and therefore does not warrant a visit to the doctor (Burgess et al, 2001;McLeod et al, 2009;Lam et al, 2009). All this can be avoided if women have better knowledge of signs and symptoms of breast cancer, perform breast self examination correctly and have proactive help-seeking behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Everywhere, a lack of education and awareness, affordability and availability of treatment are the main factors preventing patients from being diagnosed early enough 7,8 . Given all this, it is alarming that many low-and middle-income countries are devoting more of their meagre cancer-care budgets to technology, especially through the private sector.…”
Section: A Growing Problemmentioning
confidence: 99%
“…The core technology is electronics that stretch -elastronics -made from soft plastic circuits thinner than paper that can deform without tearing, biodegrade and even heal themselves (see go.nature.com/2vtutzz). Elastronic sensors respond to touch, pressure, temperature, humidity and light, as well as to chemical and biological signals [2][3][4][5][6][7][8][9][10] .…”
Section: Testismentioning
confidence: 99%
“…The possible influence of delays in diagnosis on survival and the risk factors for delay in patients with cancer have been the subject of considerable interest and controversy for many years (Macleod et al, 2009). Survival from cancer in the United Kingdom is poorer than that of other European countries, and it has been suggested that this can be attributed to more advanced disease stage at presentation (Cancer Research UK, 2009).…”
Section: Introductionmentioning
confidence: 99%